The Investigation of Maqashid Syariah Index Determinants and its Implication Towards Worls Sustainability: A Comparison of Islamic Bank in Indonesia and Malaysia - Nurun Nadia; Muhammaf Muflih; Ruhadi Ruhadi (Journal of International Conference Proceedings, 2025)
This study investigates the impact of financial, social, and Shariah compliance dimensions on the Maqashid Syariah Index (MSI) in Islamic banks, focusing on a comparative case analysis of sixteen banks (eight from Indonesia and eight from Malaysia) during 2019-2024. The financial dimension is measured using ROA, CAR, FDR, and NPF; the social dimension is represented by ZPR and QH; and Shariah compliance is proxied by the frequency of Shariah Supervisory Board meetings. Panel data were analyzed using the Fixed Effect Model (FEM) for Indonesia and the Random Effect Model (REM) for Malaysia. The results indicate that ROA, FDR, and ZPR significantly affect MSI in Indonesia, reflecting both operational efficiency and zakat-based redistribution. In Malaysia, CAR, FDR, QH, and SSB significantly influence MSI, highlighting the importance of capital strength, social finance, and governance. Rather than generalizing to the entire Islamic banking industry, the study is framed as a country-specific comparison that illustrates how institutional and regulatory contexts shape the realization of Maqashid Syariah principles in Indonesia and Malaysia.